Preparation and characterization of biodegradable collagen – Chitosan scaffolds. (2019) - Satish Kumar, T.; Vijaya Ramu, D.; Sampath Kumar, N.S.
Abstract: Biodegradable composite was prepared by blending collagen and chitosan from aquatic resources and characterized using FTIR to determine their structural integrity. The efficiency of biocomposite was evaluated in terms of swelling, protein absorption and degradability properties. Degradation and swelling behavior of the scaffolds were decreased, while protein adsorption was increased upon amalgamation of collagen with Chitosan at 7:3 ratio. Based on the obtained results, the engineered matrix is better in scaffold properties and it provides a healthier environment can be considered as a potential candidate for tissue regeneration applications.